Desarrollo de un proceso de compostaje para el aprovechamiento de lodos resultantes de la planta de tratamiento de agua potable Francisco Wiesner Eaab-Esp (2018)
The Francisco Wiesner plant located via Calera - Cundinamarca supplies the city of Bogotá with drinking water, as part of its water purification process, specifically in the washing of the filters, sewage sludge is produced. This degree project seeks to provide a solution through the use of such waste as indicated and required by Decree 1287 of July 10, 2014, in order to mitigate environmental pollution. Initially, a characterization is made to know the current status of the waste sludge, then begins the evaluation of the composting process in a horizontal rotary drum reactor with dry grass, clearly from the company in order not to generate additional costs and also exhaust the organic waste that may be generated in it. By means of a mass balance, 3,88 kg of turf and 3,492 kg of mud were entered into the reactors in the experiment, observing a maximum increase of 35ºC in temperature and a decrease in humidity percentage of 58,24% and 55%. , 67% in reactor 1 and reactor 2, on the other hand in the white reactor or reactor 3 during the 44 days decreased to 69.3%. Based on the results obtained in the experiment, it was observed that turf favored the mesophilic phase of composting.